Duration of response to first androgen deprivation therapy, time to castration resistance prostate cancer, and outcome of metastatic castration resistance prostate cancer patients treated with abiraterone acetate. Issue 1 (January 2017) - Giacinti, Silvana; Carlini, Paolo; Roberto, Michela; Bassanelli, Maria; Strigari, Lidia; Pavese, Francesco; Aschelter, Anna M.; Felici, Alessandra; Valeriani, Maurizio; Cognetti, Francesco; Marchetti, Paolo
Abstract : Abiraterone acetate (AA) demonstrated its efficacy in the treatment of patients with metastatic castration resistance prostate cancer (mCRPC) in predocetaxel and postdocetaxel setting. However, we learn from pivotal studies that forms of primary and acquired resistance to this drug exist. Patient selection becomes so crucial to optimize treatment results. Potential predictive biomarkers have been identified but are not yet validated. In this scenario, clinical features and disease characteristics may still be of value in selecting patients for different treatments. The objective of this retrospective study was to assess whether or not a correlation between duration of response to first androgen deprivation therapy (ADT), time to castration-resistant prostate cancer (TTCRPC), and outcome of AA therapy exists. A retrospective analysis of clinical data of mCRPC patients treated with AA at two Italian cancer centers was carried out. The Kaplan–Meier method and Cox proportional hazard model were used to analyze survival data. Correlation between median duration of response to first ADT or median TTCRPC and the outcome of patients treated with AA was analyzed. From January 2015 to November 2015, data of 59 patients with mCRPC were collected. We observed no differences in patient's median progression-free survival (PFS) and biochemical progression-free survival (bPFS), according to both median duration of response to first-line ADT (duration of first ADT<13 months: median PFS and bPFS were 11 and 5 months, respectively; duration of ADT≥13 months: median PFS and bPFS were 9 and 6 months, respectively) and median TTCRPC (TTCRPC<28 months: median PFS and bPFS were 8 and 5 months, respectively; TTCRPC≥28 months: median PFS and bPFS were 10 and 9 months, respectively). Overall survival, in the same group, did not differ between patients with a duration of response to first ADT over or under 13 months ( P =0.90) but in patients with a TTCRPC of 28 months or more, there was a trend toward longer survival than patients with TTCRPC less than 28 months (5-year overall survival was 74 vs. 50%; P =0.14). The duration of response to first-line ADT and the TTCRPC showed no significant association with outcome of AA therapy in patients with mCRPC. However, large prospective trials are desirable to confirm these data.